The Effect of the PECS Alternative Communication System on Vocal Speech Acquisition in Children with Autism - O.A. Popova; N.M. Filina (Moscow State University of Psychology and Education, 2021)
This article describes the positive effect of teaching the PECS (Picture exchange communication system) alternative communication system on vocal speech acquisition in children with autism spectrum disorders (ASD). Materials from an empirical study of three children with ASD and other mental disorders aged 2-4 years are presented. Measurements were made of the number of communication initiatives in children, in the form of requests using PECS pictures for three months. As a result of teaching communication using the PECS system, two out of three children had vocalization responses, in the form of words and phrasal speech. All three children demonstrated a decrease in the number of challenging behavior episodes as they learned functional communication. It was found out that learning to ask with the help of PECS has a positive effect on the vocalizations in children with autism and other mental disorders. Children trained to communicate using the PECS alternative communication system demonstrate less challenging behavior, acquire functional communication skills, which, in general, improves the quality of life of the child's family